Treatment Strategy for Pediatric Patients with Kawasaki Disease in Tertiary Referral Hospitals East Java Indonesia: A Retrospective Study - Yulistiani . (Journal of Global Pharma Technology, 2016)
Objectives : Giving therapy to pediatric patients with Kawasaki syndrome is crucial in terms of healing and prevention of potential complications. This study aim to analyzed the treatment of pediatric patients with Kawasaki Syndrome at the Tertiary Referral Hospital in East Java, Indonesia. Methodology : This retrospective study involved 16 patients aged ≤ 18 years with a diagnosis of Kawasaki Syndrome in the 2013-2016 time series. Sampling uses a non random sampling technique. Medical record data related to the history of the disease, treatment, and the resulting outcome were analyzed descriptively. Results: Child patients receive treatment therapy in different amounts, types and doses based on the status of the patient and clinical manifestations that appear. The main therapy was given to patients namely acetosal (94%) and IVIG (50%), and corticosteroids ; methylprednisolone, prednisone (44%). Oral acetosal use is 80-100 mg / kg body weight as anti-inflammatory until the fever falls and 3-5 mg / kg body weight as platelet anti-aggregation as long as the patient does not show coronary artery abnormalities within 6 to 8 weeks, the IVIG dose is 2 g / kg weigth, and the dose of methylprednisolone is 10-30 mg / kg for 3 to 10 days. Conclusion: Giving treatment adapts to the patient's needs and is in accordance with the recommended standards.Keywords: Treatment strategy, Pediatric, Kawasaki syndrome, Referral hospital.